Comparative metabolomic profiling of Arabidopsis thaliana roots and leaves reveals complex response mechanisms induced by a seaweed extract - Tran, Thi Linh Chi; Callahan, Damien L.; Islam, Md Tohidul; Wang, Yichao; Arioli, Tony; Cahill, David (Frontiers in Plant Science, 2023)
Seaweed extracts are a prominent class of biostimulants that enhance plant health and tolerance to biotic and abiotic stresses due to their unique bioactive components. However, the mechanisms of action of biostimulants are still unknown. Here, we have used a metabolomic approach to uncover the mechanisms induced following application to Arabidopsis thaliana of a seaweed extract derived from Durvillaea potatorum and Ascophyllum nodosum. Using a UHPLC-MS method, we have identified, following the application of the extract, key metabolites and systemic responses in roots and leaves across 3 timepoints (0, 3, 5 days). Our study has demonstrated that application of seaweed extract dramatically altered the metabolomic profiles of Arabidopsis and revealed differences in roots and leaves that varied across the timepoints tested. Significant alterations in metabolite accumulation or reduction were found for those belonging to broad groups of compounds such as lipids, amino acids, and phytohormones; and secondary metabolites such as phenylpropanoids, glucosinolates, and organic acids. Strong accumulations of TCA cycle and N-containing and defensive metabolites such as glucosinolates were also found revealing the enhancement of carbon and nitrogen metabolism and defence systems. We also show clear evidence of systemic responses that were initiated in the roots and resulted in metabolic alterations in the leaves. Collectively, our results suggest that this seaweed extract promotes plant growth and activates defence systems by altering various physiological processes at the individual metabolite level.